Niche unfilling dominates the naturalization of species from intercontinentally disjunct genera - Liu, Yunpeng; Heberling, J. Mason; Wang, Zhiheng; Soltis, Douglas E.; Soltis, Pamela S. (Global Ecology and BiogeographyGlobal Ecology and Biogeography, 2023)
Abstract Aim Quantifying niche shifts of non-native species and their interactions with natives is vital in evaluating invasion risk yet remains difficult. Climate filtering and competition with native congeners are two important processes impacting niche changes and yielding contradictory predictions for the coexistence of non-native and native species. Closely related species representing the Eastern Asia (EA)?Eastern North America (ENA) floristic disjunction provide a powerful yet unexplored system for assessing the relative roles of these two processes. Here, we tested three niche change scenarios (unfilling, expansion and stable) using EA species naturalized in ENA. We aim to answer: (1) which scenario is observed for naturalized species? and (2) how has niche overlap between EA and ENA congeners changed after naturalization? Location ENA and EA. Time Period Present. Major Taxa Studied Angiosperms. Methods Niches were estimated using both occurrences and predictions generated by ecological niche models. Niche changes of naturalized species and their niche overlap with natives were measured using Schoener's D. Contributions of niche expansion and unfilling on niche changes of naturalized niches were evaluated using hierarchical partitioning and linear regressions. We further measured pairwise phylogenetic distances among EA and ENA congeners and evaluated the association with niche overlap. Results Unfilling-dominated postintroduction niche changes of the naturalized species. EA species naturalized in ENA exhibited lower niche overlap with ENA native congeners compared with native range populations in EA. These results remain when considering time since introduction and potential physical dispersal limitations interpreted by projecting suitable niche space between EA and ENA. However, dispersal limitation may contribute to the degree of niche unfilling. Main Conclusions Using intercontinental disjunct species as a study system, we found that naturalization is shaped jointly by climate filtering and competition with native congeners, providing valuable insights for evaluating invasion risk underlying global floristic exchanges.
Keywords: adaptive evolution; climate filtering; Competition; Darwin's naturalization conundrum; disjunct species; Eastern North America flora; invasive species; niche changes; niche overlap; species distribution modelling